Comparison of cardiopulmonary responses to two types of dry-land upper-body exercise testing modes in competitive swimmers - Swaine, I. L.; Winter, E. M. (European Journal of Applied Physiology, 1999)
In this study we compared cardiopulmonary responses to upper-body exercise in 12 swimmers, using simulation of the front-crawl arm-pulling action on a computer-interfaced isokinetic swim bench and arm cranking on a modified cycle ergometer. Result: Simulated swimming is the preferred form of dry-land ergometry for the assessment of swimmers.